Effects of controlled water activity on microbial community succession and flavor formation in low-salt chili mash fermentation - Dai, Linli; Wang, Xin; Ahmad, Nurul Hawa; Mah, Jae Hyung; Qin, Wen; Wei, Xinyao; Liu, Shuxiang (Multidisciplinary Digital Publishing Institute, 2026)
Although fermented seasonings play a pivotal role in improving food quality, the high sodium content of many traditional products poses considerable public health concerns, including hypertension and cardiovascular disease. This study established a low-salt fermentation strategy for Mumashan chili by regulating water activity (aw) under NaCl concentrations ranging from 4 to 12% (w/w). The aw-regulated system effectively maintained aw within ± 0.03 at both 25 and 40 °C, thereby sustaining stable microbial activity despite the reduced salt concentration. Compared with the control group 15% NaCl, the 4% NaCl treatments exhibited significantly higher total acidity (130–200 g/kg vs. 24–58 g/kg) and a faster consumption rate of reducing sugars, with MH12 achieving an 80% rate of reducing sugars by day 21. Sensory evaluation revealed a higher overall quality score for the low-salt chili mash (MH12, 7.7/10), which was associated with a balanced aroma profile and enhanced color stability (ΔE < 5). However, the elevated relative abundance of opportunistic pathogens (Klebsiella app., ~10%) highlights the necessity of strict raw material hygiene. Overall, these results validate the feasibility of aw regulation for low-salt fermentation, elucidate the associations between microbial communities and flavor development, and provide a basis for future industrial applications.